Nilai-Nilai Moderasi Beragama dalam Kurikulum Pendidikan Agama Islam Rahmatan lil’alamin tingkat Madrasah Ibtida’iyah - Siti Nurdina Awalita (Journal of Contemporary Islamic Education, 2024)
This research aims to analyze the Rahmatan Lil'alamin Islamic Religious Education curriculum model and its impact on strengthening religious moderation values in Madrasah Ibtidaiyah. In its background, this research highlights the urgency of educating the younger generation with the values of religious moderation to create a tolerant and harmonious society. The research methodology is qualitative, involving Islamic Religious Education teachers as samples, and using interviews, observation, and documentation as research instruments. The results show that the implementation of the Rahmatan Lil'alamin Curriculum Model has a positive impact in shaping student character. This model emphasizes a balanced understanding of religion, promotes tolerance through interfaith dialogue, and encourages student empowerment as agents of social change. This curriculum also emphasizes moral values and student independence, creating an educational environment that supports the formation of student characters who are moderate, tolerant, and wise in carrying out religious teachings in various life contexts.